A Relational Approach to Governing Wicked Problems From Governance Failure to Failure Governance - Selg, Peeter; Sootla, Georg; Klasche, Benjamin (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
The book initiates a relational turn in policy making and governance by developing further relational political analysis and by taking relational thinking to bear on not just analytic/descriptive issues, but also to normative/prescriptive issues. The need for such a turn, this book argues, comes from the ever-increasing relevance of addressing the so-called wicked problems of governance like climate change, COVID-19 kinds of pandemics, global economic recessions and refugee crises. The book argues for a need to rethink governance as a process from the relational point of view to spur its potential for addressing these problems. What needs to be rethought is not so much the specific tools or resources of governance, but the very issue of whether governance should be seen in terms of tools and resources in the first place. This book contributes to this discussion by consolidating the relational approaches to governance thus far and by taking them to a next - normative/prescriptive - level.
1. Introduction: A Relational Approach to Governing Wicked Problems -- Part I A Relational Definition of Wicked Problems -- 2. Aren't All Problems Wicked? Addressing the Constructive and Destructive Critiques of the Concept of Wicked Problems -- 3. From Categorical Distinctions of Policy Problems to a Relational Approach to Wicked Problems -- 4. From Governance Failure to Failure Governance: A Relational Approach to Governing Wicked Problems -- Part II The History of the Present of the Theories of the Policy Process: From Self-Action to Trans-Action -- 5. A Genealogy of Self-Active Governance in Policy Theories -- 6. Problematizing Theoretical Understandings of Problems: From Self-actionalist to Inter-actionalist Approaches in Policy Sciences -- 7. The (Re)turn to the Political: Deepening the Grasp of Contingency in the Theories of the Policy Process -- 8. Speaking Truth to Power? The (Political) Constitution of Knowledgeand Rationality in Policy-Making and Governance -- 9. From De-Problematized Expert Knowledge to Politics of Critical Dialogue: Towards Process-Relational Policy Theories -- Part III Theory and Practice of Failure Governance and Governance Failure -- 10. A Theory of Governance as Problematization and De-problematization -- 11. The Whole-of-Nation-Failure-Governance: Taiwan's Politics of Problematization of COVID-19 -- 12. Making America Do Their "Own Research" Again? Trump's Politics of De-problematization of COVID-19 -- 13. Germany's Road from Failure Governance to Governance Failure -- Part IV Concluding Remarks -- 14. In Place of Conclusions: Failing Better or Waiting for Godot in a Clumsy World of Wicked Problems?.
Keywords: Sociology; Political sociology; Political science; Sociological Theory; Political Sociology; Governance and Government; Political Theory